Continuity with change: The new editorial team and some new policies and procedures. (3rd December 2013) - ABUTALEBI, JUBIN; CLAHSEN, HARALD
<x content-type="archive" xml:space="preserve">Abstract</x> Bilingualism: Language and Cognition (BLC) is now in its seventeenth year, and what started out as a new interdisciplinary journal dedicated to the study of bilingualism has now become the leading journal in its field. The first issue of BLC was published in 1998 with François Grosjean, Jürgen M. Meisel, Pieter Muysken and Judith Kroll as founding editors. Over the years, the editorship has passed to David Green, Ping Li and Carmen Silva-Corvalán, with Jürgen M. Meisel staying on. The journal has not merely survived for almost 17 years but has thrived, enjoying a steady increase in readership and submissions, suggesting that the interdisciplinary approach of the journal and the breadth of topics that it covers are hitting the mark. The 2013 impact factor mirrors this upsurge of interest: BLC's 2013 impact factor is quoted as 2.229, which makes it the 5th ranked out of 160 journals in linguistics and the 27th out of 83 experimental psychology journals. Hence it is a pleasure to report to the BLC readership that the journal is in excellent shape. This is primarily due to the outstanding dedication of the outgoing team of editors (Ping Li, David Green, Jürgen M. Meisel and Carmen Silva-Corvalán), to whom we would like to extend our gratitude. Under their tenure BLC has grown to be the leading journal in the field. We will continue to count on their advice.